1998
DOI: 10.1089/neu.1998.15.1077
|View full text |Cite
|
Sign up to set email alerts
|

Topical Axonal Transport Blocker Vincristine Prevents Nerve Injury–Induced Spinal Neuron Sensitization in Rats

Abstract: The effect of vincristine (Vin, a fast axonal transport blocker) to prevent any alteration in the excitability of dorsal horn neurons, following peripheral nerve injury, was investigated on 31 rats: 20 with chronic constriction injury (CCI) of the sciatic nerve and 11 sham preparations. In 15 of the 20 CCI rats, a small piece of gelfoam soaked with Vin was applied to the sciatic nerve before ligation (Vin+); in the remaining 5 rats the nerve was ligated without Vin (Vin-). The 11 sham rats were 7 Vin+ and 4 Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Early after nerve injury, TNF protein and mRNA at the injury site are upregulated endoneurially primarily in nonneuronal cells (Griffin et al, 1993;Bizette et al, 1996;La Fleur et al, 1996;Wagner and Myers, 1996a;Sommer and Schäfers, 1998;Taskinen et al, 2000), and after a brief temporal delay in dorsal root ganglion (DRG) neurons (Murphy et al, 1995) and the spinal cord (DeLeo et al, 1997). Consistent with a recent report of retrograde axon transport of biotinylated TNF (Shubayev and Myers, 2001) and the observation that nonspecific inhibition of axonal transport abolished neuropathic pain in animal models (Yamamoto and Yaksh, 1993;Sotgiu et al, 1998;Cougnon-Aptel et al, 1999; but see Jakobsen and Sidenius, 1983;Miller and Spencer, 1985;Filliatreau et al, 1994;White et al, 1996;Kingery et al, 1998;Colburn and DeLeo, 1999), we hy-pothesized that TNF generated by focal nerve injury is carried by fast axonal transport to central or peripheral targets and thereby contributes to the development of pain and early pathology after peripheral nerve injury.…”
supporting
confidence: 61%
“…Early after nerve injury, TNF protein and mRNA at the injury site are upregulated endoneurially primarily in nonneuronal cells (Griffin et al, 1993;Bizette et al, 1996;La Fleur et al, 1996;Wagner and Myers, 1996a;Sommer and Schäfers, 1998;Taskinen et al, 2000), and after a brief temporal delay in dorsal root ganglion (DRG) neurons (Murphy et al, 1995) and the spinal cord (DeLeo et al, 1997). Consistent with a recent report of retrograde axon transport of biotinylated TNF (Shubayev and Myers, 2001) and the observation that nonspecific inhibition of axonal transport abolished neuropathic pain in animal models (Yamamoto and Yaksh, 1993;Sotgiu et al, 1998;Cougnon-Aptel et al, 1999; but see Jakobsen and Sidenius, 1983;Miller and Spencer, 1985;Filliatreau et al, 1994;White et al, 1996;Kingery et al, 1998;Colburn and DeLeo, 1999), we hy-pothesized that TNF generated by focal nerve injury is carried by fast axonal transport to central or peripheral targets and thereby contributes to the development of pain and early pathology after peripheral nerve injury.…”
supporting
confidence: 61%
“…The injury of the nerve induces a strong bursting neuronal response (Seltzer et al, 1991;Tal and Eliav, 1996), a crucial event triggering persistent neuronal anomalies of discharge (Sotgiu et al, 1994) Accordingly, as it has been shown with locally applied Lidocaine and Vincristine ® on the sciatic nerve, the early block of hyperactivity affects the development of the behavioral and neuronal signs of neuropathic pain quite strongly (Sotgiu et al, 1995(Sotgiu et al, , 1998.…”
Section: Discussionmentioning
confidence: 98%
“…In primary sensory neurons from the rat DRG, axonal transport delivers receptors, ion channels, sensory neuropeptides, glutamate and aspartate in both central and peripheral directions [59]. It was suggested that blockade of axonal transport can inhibit the development of neuropathic pain by blocking the signaling of peripheral injury to the central neurons [60]. In this case, P2Y 2 receptor activation through agonists would be pronociceptive through stimulation of the axonal transport.…”
Section: P2y Receptors and Painmentioning
confidence: 99%